Enhancing the production of poly-γ-glutamate in Bacillus subtilis ZJS18 by the heat- and osmotic shock and its mechanism. Issue 10 (2nd November 2020) - Song, Yichao; Zhang, Yishu; He, Min; Liu, Hang; Hu, Chunyu; Yang, Liuzhen; Yu, Ping
Abstract: Poly-γ-glutamate (γ-PGA) is a natural macromolecule peptide, and is widely used in the food, medicine, and pharmaceutical industries. In this study, heat- and osmotic shock were used to improve the production of γ-PGA in Bacillus subtilis ZJS18, and its molecular mechanism was explored. The results indicated that the heat- and osmotic shock significantly promoted the production of γ-PGA owing to the stress response of B. subtilis cells to adverse environment. The highest concentrations of γ-PGA reached 14.53 and 15.98 g/l under heat- and osmotic shock, respectively. The activities of five enzymes related to the metabolism of the endogenous glutamate were determined and analyzed. It was found that the activities of glucose-6-phosphate dehydrogenase, isocitrate dehydrogenase, glutamate dehydrogenase and glutamate synthase were significantly altered during heat- and osmotic shock, while the activity of α-ketoglutarate dehydrogenase only showed a little alteration. This study provides a basis for the industrial production and use of γ-PGA, and for understanding its biosynthetic mechanism in B. subtilis ZJS18.